REKAYASA PERANGKAT LUNAK INVENTORY BARANG DENGAN METODE FAST PADA PETSHOP SALSA DI BANDAR LAMPUNG - Pitrawati .; Verawati .; Riska Bilgisa Putri (Jurnal informasi dan komputer, 2022)
Petshop Salsa in Bandar Lampung is a business engaged in sales. In sales activities there is processing of inventory data of goods. In the management of goods, PetShop Salsa has not utilized the Database Management System where all business process activities in processing goods are carried out manually, causing the process of recording goods both incoming and outgoing goods to be ineffective. This resulted in the reporting of inventory items that could not be done in a timely manner. The purpose of this study is to build an inventory application that is able to facilitate the process of inputting inventory, both incoming goods and outgoing goods so that inventory reports can be made effectively and on time. The method used in this study is the FAST (Framework For The Application System Thinking) method with Unified Modeling Language system design, namely Usecase Diagrams, Activity Diagrams, and Class Diagrams. The results of this study are the realization of an inventory application using the FAST method at Petshop Salsa in Bandar Lampung which can help process goods processing transactions more effectively and on time.